Studying the Problems and Needs of Students Towards the Service of Department of Technical Education Management, Faculty of Technical Education, King Mongkut’s University of Technology North Bangkok - Yodkammee, Walaiporn; Hanrinth, Chayanid (Journal of Technical and Engineering Education, 2023)
The objectives of this research were: 1) to study the problems of students towards the services of the Department of Technical Education, 2) to study the needs of students towards the services of the Department of Technical Education, 3) to comparing the differences of students’ problems towards the services of the Department of Technical Education Administration, Faculty of Industrial Education King Mongkut’s University of Technology North Bangkok classified by gender, age, level of education, and marital status, 4) to find the relationship of students’ needs towards the services of the Department of Technical Education Administration in Faculty of Industrial Education King Mongkut’s University of Technology North Bangkok classified by gender, age, level education and marital status. The population is the current graduate students and alumni of the Department of Technical Education Administration in Faculty of Industrial Education, King Mongkut’s University of Technology North Bangkok, 41 people. The research tool was a questionnaire. The data was analyzed using the simple statistical mean, standard deviation, the two-way discrete mean of difference analysis by t-test and one-way analysis of variance (Anova) The was analysed by correlation Chi Square (χ2). The result’s of the study found that the broblems of Faculty of Industrial Education King Mongkut’s University of Technology North Bangkok, the overall has the first three rankings as: 1) Internet system is efficient and sufficient, 2) Teaching equipment in the research room, and 3) Teaching equipment in the classroom. The needs of students regarding the services of the Department of Technical Education Administration include wanting friendliness in the service of department staff. The classroom environment should have an appropriate temperature. and have a computer network sufficient for use and there is a need for textbooks/books/dissertations in the research room Problems of students regarding the services provided by the Department of Technical Education Administration The most include Service personnel are polite, friendly, and friendly. Statistically significant at the .05 level.